2016
DOI: 10.1016/j.ajic.2016.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a pulsed xenon ultraviolet light device for isolation room disinfection in a United Kingdom hospital

Abstract: PX-UV use decreased bioburden in patient discharge rooms and on agar plates spiked with MDROs. The implementation of the PX-UV device was well received by hospital cleaning and ward staff, with minimal disruption to patient flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 23 publications
1
60
0
1
Order By: Relevance
“…Therefore, further data are needed to clearly determine the benefits of UV light, but enhanced terminal cleaning may be part of the solution. Some of the drawbacks for the use of automated methods has been cost‐effectiveness and logistical problems, including the ability of the systems to reach certain areas, the need for furniture rearrangement in the rooms for its use, and longer cleaning times of an average 1 hour per room . More recently, we were able to demonstrate equivalent efficiency in reduction of colony counts (approximately 73%) on high‐touch surface areas between cycles of 2 and 8 minutes using the PX‐UV system at a single position in the operating rooms …”
Section: Environmental Cleaningmentioning
confidence: 90%
“…Therefore, further data are needed to clearly determine the benefits of UV light, but enhanced terminal cleaning may be part of the solution. Some of the drawbacks for the use of automated methods has been cost‐effectiveness and logistical problems, including the ability of the systems to reach certain areas, the need for furniture rearrangement in the rooms for its use, and longer cleaning times of an average 1 hour per room . More recently, we were able to demonstrate equivalent efficiency in reduction of colony counts (approximately 73%) on high‐touch surface areas between cycles of 2 and 8 minutes using the PX‐UV system at a single position in the operating rooms …”
Section: Environmental Cleaningmentioning
confidence: 90%
“…Specifically, photodynamic inactivation (PDI) has been shown to be effective in the treatment of different bacteria, including antimicrobial resistant strains of bacteria (Maclean et al, 2010; Luksiene and Paskeviciute, 2011; Endarko et al, 2012; Murdoch et al, 2012; Bumah et al, 2015; Hosein et al, 2016). In the case of L. monocytogenes , light can decrease cell numbers in liquid culture, on surfaces and decrease its biofilm production meaning that PDI could be a very useful way of treating L. monocytogenes contamination in the food production environment (Murdoch et al, 2012; McKenzie et al, 2013; O’Donoghue et al, 2016).…”
Section: Methods Of Controlling L Monocytogenesmentioning
confidence: 99%
“…Light has previously been used as a method of bacterial decontamination both within clinical environments and on food products (Ozer and Demirci, 2006; Maclean et al, 2010; Hosein et al, 2016; Xu and Wu, 2016) and therefore may be useful as a means of controlling L. monocytogenes contamination within the food industry. Recently it has been shown that blue light triggers the activation of the GSR within L. monocytogenes and therefore should be considered as a stress for the bacterium (Ondrusch and Kreft, 2011; Tiensuu et al, 2013).…”
Section: Stresses Encountered In Foodmentioning
confidence: 99%
“…Pulsed xenon ultraviolet (PX-UV) is proven as an effective tool for disinfection of pathogens in various hospital settings, including wards [2][3][4][5][6], operating rooms [7], surgical sites [8,9], nursing rooms [10], human milk feeding rooms [11], and burns units [12]; and this disinfectant effect also applies to clinical laboratories and blood sampling rooms in China [13,14]. However, the effectiveness of PX-UV in disinfection of a hospital animal laboratory is unstudied.…”
Section: Introductionsmentioning
confidence: 99%